Pengaruh konsumsi daun kacang Panjang terhadap produksi ASI Ibu - Gustien Siahaan; lailatul Badriyah (Universitas Batanghari Jambi, 2022)
Exclusive breastfeeding coverage in Indonesia has not reached the expected number (<80%) that mothers stop breastfeeding due to lack of milk production, for this reason, giving long bean leaves has the potential to stimulate oxytocin and prolactin hormones such as alkaloids, saponins, polyphenols, steroids, flavonoids and other substances. the most effective in increasing and smoothing the production of breast milk. This study aims to determine the effect of consumption of long bean leaves on mother's milk production. This study is a quasi- experimental study with a random cluster design pretest and posttest. This research was conducted in the Sungai Clear Village, Muara Curb District, Tebo Regency, which was carried out on February 17 - March 5, 2022. The population in this study were all breastfeeding mothers who lived in Sungai Clear Village, Muara Rab District, Tebo Regency, as many as 32 people. The sample in this study were 32 people who were taken by total sampling technique. Collecting data by observing breast milk production. Data were analyzed by univariate and bivariate using Wilcoxon statistical test. The results showed that there is an effect of consumption of long bean leaves on mother's milk production in Sungai Jernih Village, Muara Tabir District, Tebo Regency in 2022 with a p value of 0.000. It is hoped that the results of this study can provide information to health workers, especially midwives, in increasing breast milk production by providing counseling to breastfeeding mothers and recommending consuming long bean leaves as a method with ingredients that are easily available and not harmful to maternal health.